ORGANOLEPTIC AND CHEMICAL CHARACTERIZATION OF BANANA PEEL FLOUR ADDING TO SOFT CANDY PRODUCTS - Fatkhiyatur Rizkiyah; Maylina Ilhami Khurniyati (Universitas Veteran Bangun Nusantara, 2026)
The purpose of this research was to analyze the chemical and organoleptic properties of soft candy after adding banana peel flour. A Completely Randomized Design (CRD) with three replications was used in the investigation. The design consisted of a single element, namely the concentration of banana peel flour (0-40 g). Chemical analyses of moisture and ash content were among the measured characteristics, in addition to organoleptic evaluations (color, scent, taste, and texture) based on a hedonic scale. An ANOVA test was performed on the data with a significance level of 5%. Adding banana peel flour significantly changed the ash amount and flavor, but had no discernible influence on color, fragrance, texture, or moisture content, according to the data. Treatment P1 had the greatest moisture content at 12.64% and treatment P5 the lowest at 10.38%; nevertheless, there was no statistically significant difference between the two (p>0.05). There was a very significant difference (p<0.05) in the ash content, which rose with increasing concentrations of banana peel flour, reaching a peak of 2.85% in P5 and a minimum of 1.61% in P1. Since the moisture and ash levels were within the stipulated limits, all treatments were deemed to meet the SNI quality criteria for soft candy.